THE RELEVANCY OF ENGLISH IN CONTEXT FOR SMA/MA STUDENT YEAR ONE TEXTBOOK TO THE CURRICULUM USED - Nisak, Qudwatin (Universitas Islam Negeri Banda Aceh, 2013)
To improve the quality of English education in Nanggroe Aceh Darussalam (NAD), the Department of Education of NAD as policymaker has made some efforts, among others, sending some teachers for overseas training and also conducting in-service training in designing English teaching material. One of the results of the projects done by the Department of Education of NAD is an English textbook entitled